Diversity in the Workplace: A Systematic Literature Review of Global Research: English - Venesia Venesia; Ramadania Ramadania (International Journal of Multidisciplinary Sciences and Arts, 2025)
Employee diversity has increasingly been recognized as a strategic factor influencing organizational innovation, performance, and sustainability across sectors and countries. However, previous studies reveal limited geographical coverage and a predominant focus on demographic dimensions. This study aims to systematically review the global literature on employee diversity and identify emerging thematic, methodological, and theoretical trends. This research employed a Systematic Literature Review (SLR) using the PRISMA approach to ensure a transparent and rigorous selection and analysis process. Data were collected from the Scopus database for the period 2020–2025, yielding 56 eligible peer-reviewed articles. The analysis examined research contexts, theoretical frameworks, methodologies, core variables, and empirical findings. The results indicate that employee diversity research is dominated by themes of diversity management, gender equity, inclusive leadership, and psychological safety. Intersectionality and Social Identity Theory are the most frequently applied frameworks, while quantitative methods, particularly Structural Equation Modeling, remain dominant. Notable gaps include underrepresentation of developing countries, insufficient integration of cross-cultural perspectives, and inconsistent measurement of psychosocial variables. This review concludes that managing diversity should be viewed as a strategic organizational resource rather than a moral obligation. The study proposes the Multidimensional Diversity Integration Framework (MDIF) to integrate social, psychological, and cultural dimensions into inclusive and sustainable human resource management practices.